Horizontes do trabalho decente no Carajás: ações e métodos judiciais e extrajudiciais de combate ao trabalho análogo ao de escravo na implementação da Agenda Regional de Trabalho Decente de Carajás - SAMPAIO, Alessandra Kelly Neves (2023)
The present work aims to point out and evaluate how preventive actions and judicial and extrajudicial repressive methods have been applied by the responsible actors as measures to implement the Lines of Action embodied in the Decent Work Regional Agenda (DWRA) of Carajás. To do so, the year of 2018 was chosen as a time frame, as it was the year the Agenda was launched. Furthermore, considering that the DWRA of Carajás was designed in light of the Sustainable Development Goals (SDG) of the 2030 Agenda, it will therefore seek to evaluate the implementation of the Target 8.7 in the region, which is also related to the guarantee of Decent Work through the fight against modern slavery. This way, it is intended to draw a design that allows to evaluate the status of the implementation of Decent Work Agendas in the Carajás region, in the southeast of the state of Pará, understanding the current situation of the fight against modern slavery in the region, as well as pointing out, more specifically, which Lines of Action from the DWRA of Carajás are already being implemented, which require greater efforts to be implemented and which are not yet being implemented by the responsible actors.